2020
DOI: 10.1080/2162402x.2020.1824644
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factor V is a marker of tumor-infiltrating immune cells in breast cancer

Abstract: Background: Factor (F) V is an essential cofactor in blood coagulation, however, F5 expression in breast tumors has also been linked to tumor aggressiveness and overall survival. The specific role of FV in breast cancer is yet unknown. We therefore aimed at dissecting the biological relevance of FV in breast cancer. Methods: Gene expression data from a Scandinavian breast cancer cohort (n = 363) and the cancer genome atlas (TCGA) (n = 981) and 12 replication cohorts were used to search for F5 co-expressed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Garber et al found that F5 gene variation was associated with breast cancer. The F5 expression was enriched in breast cancer and was associated with overall survival [27]; moreover, the F5 gene was associated with the risk of thrombosis in cancer patients [28]. F5 is also associated with the risk of thrombosis in patients with metastatic androgen-dependent prostate cancer who undergo diethylstilbestrol and docetaxel chemotherapy [29].…”
Section: Discussionmentioning
confidence: 99%
“…Garber et al found that F5 gene variation was associated with breast cancer. The F5 expression was enriched in breast cancer and was associated with overall survival [27]; moreover, the F5 gene was associated with the risk of thrombosis in cancer patients [28]. F5 is also associated with the risk of thrombosis in patients with metastatic androgen-dependent prostate cancer who undergo diethylstilbestrol and docetaxel chemotherapy [29].…”
Section: Discussionmentioning
confidence: 99%
“…Tumors with high expression of F5 exhibit an increased inflammatory infiltration, with lymphoid and myeloid cells. This is probably related to a better immune anti-tumor response, which could explain the better prognostic of such tumors, suggesting a potential opportunity for novel therapeutic strategies [ 57 ]. Frizzled 6 belongs to a family of transmembrane receptors for Wnt signaling proteins, frequently amplified in breast cancer, mainly in triple-negative molecular type [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that FV levels are increased in breast cancer tissue compared to normal breast tissue and that the F5 mRNA levels are higher in ER negative breast tumors, suggesting a role of FV in breast cancer. Moreover, high levels of F5 mRNA in breast tumors are associated with a better overall breast cancer survival 8 and relapse-free survival 7 . Studies on the molecular mechanisms regulating FV levels in breast cancer are lacking, however, estrogen-containing hormone treatment has been shown to increase F5 mRNA levels in post-menopausal women previously 18 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…We have previously reported that breast cancer patients with basal tumors (which are triple negative of the hormone receptors) expressing higher levels of F5 had better overall survival rates compared to patients with lower F5 tumor expression 8 . Moreover, high F5 in tumors from breast cancer patients has been shown to be associated with an improved relapse-free survival, independent of breast cancer subtype 7 . Here we also report that relapse-free survival in patients with ER positive breast cancer expressing higher levels of F5 are associated with increased survival.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation